Single isocenter dynamic conformal arcs-based radiosurgery for brain metastases: Dosimetric comparison with Cyberknife and clinical investigation - Yoshiko Oshiro; Masashi Mizumoto; Yuichi Kato; Yukihiro Tsuchida; Koji Tsuboi; Takeji Sakae; Hideyuki Sakurai (Technical Innovations & Patient Support in Radiation Oncology, 2024)
Purpose: To compare the dosimetric quality of automatic multiple brain metastases planning (MBM) with that of Cyberknife (CK) based on the clinical tumor condition, such as the tumor number, size, and location. Methods: 76 treatment plans for 46 patients treated with CK were recalculated with the MBM treatment planning system. Conformity index (CI), homogeneity index (HI), gradient index (GI), lesion underdosage volume factor (LUF), healthy tissue overdose volume factor (HTOF), geometric conformity index (g) and mean dose to normal organs were compared between CK and MBM for tumor number, size, shape and distance from the brainstem or chiasm. Results: The results showed that the mean brain dose was significantly smaller in MBM than CK. CI did not differ between MBM and CK; however, HI was significantly more ideal in CK (p = 0.000), and GI was significantly smaller in MBM (P = 0.000). LUF was larger in CK (p = 0.000) and HTOF and g was larger in MBM (p = 0.003, and 0.012). For single metastases, CK had significantly better HTOF (p = 0.000) and g (p = 0.002), but there were no differences for multiple tumors. Brain dose in MBM was significantly lower and CI was higher for tumors < 30 mm (p = 0.000 and 0.000), whereas HTOF and g for tumors < 10 mm were significantly smaller in CK (p = 0.041 and p = 0.016). Among oval tumors, brain dose, GI and LUF were smaller in MBM, but HTOF and g were smaller in CK. There were no particular trends for tumors close to the brainstem, but HTOF tended to be smaller in CK (0.03 vs. 0.29, p = 0.068) for tumors inside the brainstem. Conclusions: MBM can reduce the brain dose while achieving a dose distribution quality equivalent to that with CK.